Record of Discussions Forty Ninth Meeting National Development Council - Planning Commission (Planning Commission, 2001)
Shri K.C. Pant, Deputy Chairman, Planning Commission while welcoming the participants said that the process of Plan Development has harmonized our aspirations with available resources for a common national goal. The National Development Council, at the apex of our policy making structure, has been guiding the course of this development process. It is a forum, which has fostered consensus building amidst diverse and varying perspectives. The plans embody this spirit of cooperation and mutual understanding. Indians could be proud of this unique example of democratic decision-making in a federal polity.
Government of India Planning Commission
Government of India Planning Commission